2011
DOI: 10.1209/0295-5075/95/34004
|View full text |Cite
|
Sign up to set email alerts
|

Birefringence-induced polarization-independent and nearly all-angle transparency through a metallic film

Abstract: We propose an birefringence route to perfect electromagnetic (EM) wave tunneling through a metallic film which relies on homogeneous birefringent coatings with moderate and positive parameters only. EM transparency is achieved in such an birefringent-metal-birefringent (BMB) structure for both polarizations and over nearly all incident angles. The stringent restrictions in conventional dielectric-metal-dielectric media, i.e., dielectrics with extremely negative permittivity, high magnetic field and polarizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The phenomenon of tunneling of electromagnetic waves through opaque layers has always been a fascinating and somehow counterintuitive subject. Tunneling structures based on an extremely high negative permittivity layer coated by high positive permittivity layers [1], a negative permittivity slab sandwiched between birefringence layers [2], conjugate matched pair of negative permittivity and negative permeability slabs [3], a negative permittivity slab paired with a double-positive uniaxial slab [4], and permittivity-near-zero bi-layers [5] have been reported. Recently, it was revealed that the phenomenon of electromagnetic wave tunneling can happen through electrically long distances [6].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of tunneling of electromagnetic waves through opaque layers has always been a fascinating and somehow counterintuitive subject. Tunneling structures based on an extremely high negative permittivity layer coated by high positive permittivity layers [1], a negative permittivity slab sandwiched between birefringence layers [2], conjugate matched pair of negative permittivity and negative permeability slabs [3], a negative permittivity slab paired with a double-positive uniaxial slab [4], and permittivity-near-zero bi-layers [5] have been reported. Recently, it was revealed that the phenomenon of electromagnetic wave tunneling can happen through electrically long distances [6].…”
Section: Introductionmentioning
confidence: 99%
“…The physical origins are usually ascribed to the excitation of surface plasmons (SPs) [1]- [3] (or spoof SPs (SSPs) for highly conducting structure [4]), and/or the Fabry-Pérot (FP)-like resonances in the defects [5]- [7]. Additional mechanism to tunnel light by the high magnetic field concentrated around the metallic films is also evidenced [8], [9]. However, SMG usually supports narrowband transmission because of its resonant nature.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] While for a seamless thin metallic film, only a few attempts have been done to enhance its transmission. 12,13 Recently, a symmetric multiple-layered nanostructure has been demonstrated to achieve broadband transparency for a continuous Ag film. 14 In view of the fabrication, it is quite difficult to make highly symmetric structures on both sides of the Ag film.…”
mentioning
confidence: 99%